2009
DOI: 10.1002/ajim.20689
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of occupational burns in Oregon, 2001–2006

Abstract: Occupational burns continue to be a problem for working Oregonians, and the use of additional data sources outside of WC augments our surveillance system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In addition, future studies including factors outside of work will be important. The higher risk of work-related injuries in younger workers has been reported in Western countries 1,17,26,40,41) . Some previous studies on workers in some industries reported that age was a risk factor for LBP 8,33,42,43) , while other studies reported no association between age and LBP 8,39) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, future studies including factors outside of work will be important. The higher risk of work-related injuries in younger workers has been reported in Western countries 1,17,26,40,41) . Some previous studies on workers in some industries reported that age was a risk factor for LBP 8,33,42,43) , while other studies reported no association between age and LBP 8,39) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to involve a heavy workload and carry risks of musculoskeletal disorders [5][6][7][8] . Kitchen workers are also reported to be one of the highest risk occupational groups for workrelated injuries because of the nature of their work and the types of materials handled 14,15,26,27) . School lunches are provided for all pupils five days a week at primary schools in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of food service burn injuries is as high as 5.9 per 10 000 workers. In some states, such as Oregon, it is the highest rate reported for any industry 69 . The most likely causes of burns are the spilling of hot liquids and contact with hot cooking oil or hot equipment 70 .…”
Section: Occupational Health In Restaurant Workmentioning
confidence: 99%
“…Some investigators have used multiple data sources to attempt to capture more incidents than may be captured by any one data source alone. Walters [2009] used hospitalized claims from workers' compensation and records from a regional burn center to characterize occupational burns in Oregon. Researchers in Kentucky [Bunn et al, 2007] linked hospital discharge and WC data to describe work-related injuries in that state.…”
Section: Health Claims and Healthcare System Datamentioning
confidence: 99%